Doxorubicin-Induced Oxidative Stress and Endothelial Dysfunction in Conduit Arteries Is Prevented by Mitochondrial-Specific Antioxidant Treatment - Zachary S. Clayton; Vienna E. Brunt; David A. Hutton; Nicholas S. VanDongen; Angelo D’Alessandro; Julie A. Reisz; Brian P. Ziemba; Douglas R. Seals (2020)
Doxorubicin (DOXO) chemotherapy increases risk for cardiovascular disease in part by inducing endothelial dysfunction in conduit arteries. However, the mechanisms mediating DOXO-associated endothelial dysfunction in (intact) arteries and treatment strategies are not established. We tested the hypothesis that DOXO impairs endothelial function in conduit arteries via excessive mitochondrial reactive oxygen species (ROS) and that these effects could be prevented by treatment with a mitochondrial-targeted antioxidant (MitoQ). Endothelial function (endothelium-dependent dilation [EDD] to acetylcholine) and vascular mitochondrial ROS were assessed 4 weeks following administration (10 mg/kg intraperitoneal injection) of DOXO. A separate cohort of mice received chronic (4 weeks) oral supplementation with MitoQ (drinking water) for 4 weeks following DOXO. EDD in isolated pressurized carotid arteries was 55% lower 4 weeks following DOXO (peak EDD, DOXO: 42 ± 7% vs. sham: 94 ± 3%; p = 0.006). Vascular mitochondrial ROS was 52% higher and manganese (mitochondrial) superoxide dismutase was 70% lower after DOXO versus sham (p = 0.0008). Endothelial function was rescued by administration of the mitochondrial-targeted antioxidant, MitoQ, to the perfusate. Exposure to plasma from DOXO-treated mice increased mitochondrial ROS in cultured endothelial cells. Analyses of plasma showed differences in oxidative stress-related metabolites and a marked reduction in vascular endothelial growth factor A in DOXO mice, and restoring vascular endothelial growth factor A to sham levels normalized mitochondrial ROS in endothelial cells incubated with plasma from DOXO mice. Oral MitoQ supplementation following DOXO prevented the reduction in EDD (97 ± 1%; p = 0.002 vs. DOXO alone) by ameliorating mitochondrial ROS suppression of EDD. DOXO-induced endothelial dysfunction in conduit arteries is mediated by excessive mitochondrial ROS and ameliorated by mitochondrial-specific antioxidant treatment. Mitochondrial ROS is a viable therapeutic target for mitigating arterial dysfunction with DOXO.